Membangun Karakter Kebersamaan Siswa Melalui Permainan Angklung - Sucipto, Sucipto (International Journal Labs, 2025)
This study aims to analyze the effectiveness of angklung playing in building the character of togetherness among sixth-grade students at SDN Junrejo 02 Batu City. Angklung as a traditional Indonesian musical instrument that applies the philosophy of